A Comparative Study Between Malaysia And The European Union On Social Responsibility - Kwok, Onn Jui (2006)
This study sets out to evaluate and compare the state of CSR in Malaysia, as a developing nation with the European Union (EU). In this research, the United Kingdom (UK) as representative of the EU will serve as reference for comparison.